The ancient Mediterranean environment between science and history - Harris, William V. (Columbia Studies in the Classical Tradition, 2013)
Scientists, historians and archaeologists are at last beginning to collaborate seriously on studies of the long-term history of the environment. The fruit of an international conference held in Rome in 2011, The Ancient Mediterranean Environment between Science and History brings together scientists and scholars who are interested in the interaction of their several disciplines as well as in specific problems such as the effects of climate change and other environmental factors on historical developments and events, the sources of the energy and fuel used in ancient civilizations, and the effects of humans on the lands around the Mediterranean. The collection balances broad Mediterranean-wide studies and tightly focused studies of particular regions in Italy and Jordan.